PERUBAHAN SOSIAL PADA PETANI KELAPA (Studi kasus Petani Kelapa di Desa Senduk, Kecamatan Tombariri) - Richi Romel Sembel; Martha M. Sendow; Welson M. Wangke; Jean F.J. Timban (Sam Ratulangi University, 2015)
The purpose of this study was to determine how social changes in the lives of coconut farmers in the village Senduk over the last 10 years. This study uses a case study. Data collected in the form of primary data and secondary data. Primary data was collected by means of in-depth interviews on 20 respondents who are coconut farmers. The primary data is regarding the farmer characteristics and the occuring of social change process. While secondary data such as population growth comes from the Senduk village office. Primary data were analyzed descriptively. The research results showed that social change in the form of social order has been a shift. In this case the shift in social norms that lead to behavioral changes in Senduk coconut farmers in the village. The results showed that social change in the form of social order has been a shift. In this case the shift in social norms that lead to behavioral changes in society Senduk coconut farmers in the village. Likewise, there has been a change in people's lifestyles, people are more likely to implement a consumptive lifestyle. Coupled with the influx of new technologies have led to reduce a directly social interaction and also farmers began to abandon their traditions. Population growth that occurred over the last 10 years has led to an increase in density which in turn leads to the village of Senduk government should expand the area of ​​new settlements. The expansion of residential areas has an impact on agricultural land with the narrowing of agricultural land due to the transfer of use of agricultural land to residential land.